Asymptotic solutions of the Dirichlet problem for the heat equation with impulses - Matarazzo, G. (Ukrains’kyi Matematychnyi Zhurnal, 2006)
We propose an algorithm for the construction of asymptotic expansions for solutions of the Dirichlet problem for the heat equation with impulses.